2022
DOI: 10.1097/acm.0000000000004718
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Medical Students to Address Health Disparities Through Longitudinally Integrated Social Justice Curricula: A Systematic Review

Abstract: Purpose The education of health care professionals is a contributing factor to persistent health disparities. Although medical students are expected to understand racism, classism, and other social and structural drivers of health (SDH), standardization and best practices for teaching these concepts are lacking. Some medical schools are adopting social justice curricula (SJC) that prioritize health equity in teaching students to recognize SDH and preparing them to address the consequent health disparities. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A further challenge for the students in the current study related to finding time in a busy academic schedule to participate in the programme despite the student-identified necessity of the programme. This highlights the need for medical schools to formally incorporate anti-racism and social justice education into the timetable, the benefits of which have been highlighted in a recent systematic review [ 50 ]. The review demonstrated improved knowledge and skills related to understanding and tackling social injustice amongst medical students and that graduates were better prepared to work with underserved populations when they have dedicated teaching regarding the impact of social injustice on health.…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge for the students in the current study related to finding time in a busy academic schedule to participate in the programme despite the student-identified necessity of the programme. This highlights the need for medical schools to formally incorporate anti-racism and social justice education into the timetable, the benefits of which have been highlighted in a recent systematic review [ 50 ]. The review demonstrated improved knowledge and skills related to understanding and tackling social injustice amongst medical students and that graduates were better prepared to work with underserved populations when they have dedicated teaching regarding the impact of social injustice on health.…”
Section: Discussionmentioning
confidence: 99%
“…An intentional effort to build and maintain trust and reduce the impacts of medical mistrust on patient outcomes is needed. Interventions should follow established models of community-academic engagement (20), increase diversity in the biomedical workforce (21), enhance medical school curricula (22), and improve patient-centered communication (23).…”
Section: We Must Establish Trust In the System And Mced Testsmentioning
confidence: 99%
“…11,15 A growing body of evidence, including the TRC and UNESCO calls to action, suggests JEDI training is needed to give HCPs the knowledge and skills to promote AO and health justice, and deliver culturally safe care for diverse populations to improve health outcomes. 9,10,[15][16][17] Integration of JEDI and AO concepts in health care education can have meaningful impact. For example, in medical schools where social justice is integrated into core curricula, students are more likely to learn about drivers of health disparities, recognize their own biases, and connect patients with appropriate resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in medical schools where social justice is integrated into core curricula, students are more likely to learn about drivers of health disparities, recognize their own biases, and connect patients with appropriate resources. 16 It is necessary for all HCPs to enter practice with an understanding of the benefits of providing culturally safe care. 17 Preparing students in entry-level health care professional programs with the skills to promote JEDI concepts and dismantle oppressive systems and structures can help reduce health disparities, enhance patient satisfaction, and improve intervention compliance and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation